Interdependensi Informasi Fundamental Keuangan Terhadap Harga Saham Perusahaan (Analisis Data pada Perusahaan Asuransi Terbuka Tahun 2008 -2012) - Putong, Iskandar (Binus Business Review, 2014)
This study analyzed the effect of fundamental information of a company such as company financial performance in the form of financial ratios, namely the coefficient of DAR, DER, ROA, ROE, OPM and NPM of the companys stock price in general, either in closing stock price (Pclose), PBV or PER. The object of research is the insurance companies listed on Indonesia stock exchanges until the analysis was conducted in 2013. The number of samples used is equal to the total population of listed companies until 2013, which publish their financial report, as many as nine companies. The type of data used are secondary data in a form of panel (pooled data). The period of data between 2008 and 2012. The analytical tool used is multiple regression and multivariate Formative Structural Equation Modeling is often called Canonical Correlation (CanCorr). By using Level Of Confident of between 90% to 99%, the results of multiple regression analysis (assuming simultaneous) showed that together all of these variables affect the financial performance of the PER and PBV, but had no effect on Pclose. By using Canonical Correlation analysis, the results showed statistically significant canonical variables of fundamental financial information firm canonical variables significantly influence to the financial performance of the company.